2021
DOI: 10.1080/13880209.2021.1944223
|View full text |Cite
|
Sign up to set email alerts
|

In vitro study on the effect of peucedanol on the activity of cytochrome P450 enzymes

Abstract: Context: Peucedanol is a major extract of Peucedanum japonicum Thunb. (Apiaceae) roots, which is a commonly used herb in paediatrics. Its interaction with cytochrome P450 enzymes (CYP450s) would lead to adverse effects or even failure of therapy. Objective: The interaction between peucedanol and CYP450s was investigated. Materials and methods: Peucedanol (0, 2.5, 5, 10, 25, 50, and 100 lM) was incubated with eight human liver CYP isoforms (CYP1A2, 2A6, 3A4, 2C8, 2C9, 2C19, 2D6, and 2E1), in pooled human liver … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Nowadays, the pharmacological studies on PEU are few. An in vitro study showed that PEU was a non-competitive inhibitor of cytochrome3A4 (CYP3A4) and competitive inhibitors of CYP1A2 and CYP2D6, and its IC 50 values for these three CYP450 enzymes were 6.03, 13.57, and 7.58 μM, respectively [15] . Further, PEU isolated from Toddalia asiatica (L.) Lam.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, the pharmacological studies on PEU are few. An in vitro study showed that PEU was a non-competitive inhibitor of cytochrome3A4 (CYP3A4) and competitive inhibitors of CYP1A2 and CYP2D6, and its IC 50 values for these three CYP450 enzymes were 6.03, 13.57, and 7.58 μM, respectively [15] . Further, PEU isolated from Toddalia asiatica (L.) Lam.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, traditional Chinese medicine (TCM) plays an important role in the treatment of diabetes and often is used to treat T2DM combined with drugs (Cao et al., 2021; Chen et al., 2021; Luo et al., 2022). Gegenqinlian decoction (GQD), a classical prescription of TCM, originated from Shanghanlun and consists of Gegen (Puerariae Lobatae Radix), Huanglian (Coptidis Rhizoma), Huangqin (Scutellariae Radix), and Gancao (Glycyrrhizae Radix et Rhizoma) (Han et al., 2017; Lin et al., 2022; Zhang, Li, et al., 2021). It has multi‐pharmacological effects, such as a lipid‐lowering effect, hypoglycemic effect, and improves intestinal flora (Tian et al., 2021; Zhang, Xu, et al., 2021; Zhou et al., 2021).…”
Section: Introductionmentioning
confidence: 99%